Rapid Communication: Pianists exhibit enhanced memory for vocal melodies but not piano melodies. Issue 5 (May 2015) - Weiss, Michael W.; Vanzella, Patrícia; Schellenberg, E. Glenn; Trehub, Sandra E.
Nonmusicians remember vocal melodies (i.e., sung to la la ) better than instrumental melodies. If greater exposure to the voice contributes to those effects, then long-term experience with instrumental timbres should elicit instrument-specific advantages. Here we evaluate this hypothesis by comparing pianists with other musicians and nonmusicians. We also evaluate the possibility that absolute pitch (AP), which involves exceptional memory for isolated pitches, influences melodic memory. Participants heard 24 melodies played in four timbres (voice, piano, banjo, marimba) and were subsequently required to distinguish the melodies heard previously from 24 novel melodies presented in the same timbres. Musicians performed better than nonmusicians, but both groups showed a comparable memory advantage for vocal melodies. Moreover, pianists performed no better on melodies played on piano than on other instruments, and AP musicians performed no differently than non-AP musicians. The findings confirm the robust nature of the voice advantage and rule out explanations based on familiarity, practice, and motor representations.